(untitled) (Palimpsesto, 2017)
The primary purpose of the following research paper is to reconstruct and analyze the arguments made in the public sphere by agents related to Catholic thinking on property rights in Chile in the early 1960s. While a shared assessment as to the need for and the imminence of structural reform is present, the debates here presented are also influenced by different presentations on the nature of property rights, on its doctrinal legitimacy and limits on the Christian message and the ecclesiastical Magisterium, on its ontological features, and finally on the effective alternatives to either the liberal or Marxist predominance in property rights management.